Guidelines for Acquiring and Reporting Clinical Neurospectroscopy - Lin, Alexander; Tran, Thao; Bluml, Stefan; Merugumala, Sai; Liao, Hui-Jun; Ross, Brian D. (Seminars in Neurology, 2012)
Since the advent of CPT 76390 in 1998, magnetic resonance spectroscopy (MRS) of the brain, or neurospectroscopy, has moved from the realm of academic research into that of the clinical world. All major MR manufacturers have aided in the endeavor by automating neurospectroscopy so that it no longer requires an MR physicist and is a push-button technique that can be run by technologists just as a typical MR sequence. Thousands of studies have demonstrated the clinical efficacy of neurospectroscopy, and there are many medical reviews of how this technique can be applied across a wide range of neurologic disorders. However, few studies address the practical issue of acquiring and reporting neurospectroscopy in a clinical practice. Based on clinical experience at three different sites across the country and nearly two decades of applications training for technologists and radiologists at international clinical neurospectroscopy courses, the guidelines described in this article demonstrate proven protocols for clinical diagnosis and outline the strategies involved in acquiring, interpreting, and reporting clinical neurospectroscopy successfully. A standard operating procedure used across the three sites is described and high reproducibility across different platforms is shown.
Keywords: magnetic resonance spectroscopy; clinical efficacy; standardization; neurologic disease; reproducibility